A novel approach for the purification of aggregation prone proteins - Royster, Austin; Mir, Sheema; Mir, Mohammad Ayoub (PLOS ONE, 2021)
The protein aggregation is one of the major challenges of the biotechnological industry, especially in the areas of development and commercialization of successful protein-based drug products. The inherent high aggregation tendency of proteins during various manufacturing processes, storage, and administration has significant impact upon the product quality, safety and efficacy. We have developed an interesting protein purification approach that separates the functionally active protein from inactive aggregates using a detergent concentration gradient. The C-terminally His tagged nucleocapsid protein of Crimean Congo Hemorrhagic fever virus (CCHFV) has high aggregation tendency and rapidly precipitates upon purification by NiNTA chromatography. Using the new purification approach reported here, the freshly purified protein by NiNTA chromatography was further processed using a detergent gradient. In this new purification approach the active protein is retained in the low detergent concentration zone while the inactive aggregates are promptly removed by their rapid migration to the high detergent concentration zone. The method prevented further aggregation and retained the RNA binding activity in the native protein despite numerous freeze thaw cycles. This simple approach prevents protein aggregation by rapidly separating the preformed early aggregates and creating the appropriate microenvironment for correctly folded proteins to retain their biological activity. It will be of potential importance to the biotechnological industry and other fields of protein biochemistry that routinely face the challenges of protein aggregation.